A randomized phase II trial on the addition of dutasteride to combined androgen blockade therapy versus combined androgen blockade therapy alone in patients with advanced or metastatic salivary duct carcinoma – the DUCT study protocol - Jetty A. M. Weijers; Gerald W. Verhaegh; G. Lassche; Adriana C. H. van Engen-van Grunsven; Chantal M. L. Driessen; Nielka P. van Erp; Marianne A. Jonker; Jack A. Schalken; Carla M. L. van Herpen (BMC Cancer, 2024)
Abstract Background Salivary duct carcinoma (SDC) is a rare and aggressive subtype of salivary gland cancer, frequently associated with incurable recurrences and distant metastases (R/M). Proliferation of SDC relies on androgen receptor (AR) signalling, prompting the use of combined androgen blockade (CAB, i.e., luteinizing hormone-releasing hormone agonist and/or AR antagonists) to R/M SDC patients. However, only a subset of patients benefits from such treatments. We have shown that response to CAB is associated with steroid 5α-reductase 1 (SRD5A1) mRNA expression. SRD5A1 catalyses the intracellular conversion of testosterone into the more potent AR-agonist dihydrotestosterone. This conversion can be inhibited by dutasteride, a potent SRD5A1-inhibitor, which is currently prescribed for benign prostatic hyperplasia. We hypothesize that repurposing dutasteride to target AR signalling in SDC could enhance therapeutic response and clinical outcome in SDC patients. Methods This prospective, open-label, randomized controlled phase II clinical trial, is designed to investigate whether dutasteride as an adjunct drug to CAB improves response rate and clinical outcome in patients with AR-positive R/M SDC. Patients are divided in two cohorts based on their prior systemic treatments. In cohort A, CAB-naïve patients (n = 74) will be randomly assigned to either a control arm (Arm 1) receiving CAB (goserelin 10.8 mg/3m and bicalutamide 50 mg/OD) or an experimental arm (Arm 2) where dutasteride (0.5 mg/OD) is added to the CAB regimen. In cohort B, patients with disease progression after adjuvant or first-line palliative CAB therapy (max. n = 24) will receive goserelin, bicalutamide, and dutasteride to assess whether the addition of dutasteride can overcome therapy resistance. The primary endpoints are the objective response rate and duration of response. Secondary endpoints are progression-free survival, overall survival, clinical benefit rate, quality of life, and safety. Translational research will be performed to explore molecular target expression differences and their correlation with clinical outcome. Discussion The DUCT study addresses an unmet medical need by investigating the repurposing of dutasteride to enhance treatment response and improve clinical outcome for patients with R/M SDC, especially those with limited alternative treatment options, such as HER2-negative cases. By repurposing a registered low-cost drug, this trial’s findings could be readily applied into clinical practice. Trial registration Clinicaltrials.gov Identifier: NCT05513365. Date of registration: August 24, 2022. Protocol version Current protocol version 4.0, February 21, 2024.